2014
DOI: 10.1161/circinterventions.114.001479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reduction of the Pulse Rates of Fluoroscopy and CINE-Acquisition on X-Ray Dose and Angiographic Image Quality During Invasive Cardiovascular Procedures

Abstract: Background— Reducing digital pulse rates (PR) are known to reduce total energy during invasive cardiovascular procedures, which likely has benefits for patients and staff. Physicians may be reluctant to reduce these parameters because they fear a decline in image quality that could affect procedural outcomes. We sought to assess the effect of default rates of fluoroscopy (Fluoro) and CINE-acquisition (CINE) on total x-ray dose and image quality during invasive cardiovascular procedures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 22 publications
(22 reference statements)
3
32
0
Order By: Relevance
“…The median total air kerma was significantly reduced after institution of lower fluoroscopy rates, with 22% and 32% reduction in diagnostic and interventional procedures, respectively. Similar to the study by Pyne et al, 13 fluoroscopy times were not influenced by the change in pulsed frame rate. Tube angulation previously has been shown to be an important factor in radiation exposure.…”
Section: Data Supporting the Use Of Lower Pulsed Frame Ratessupporting
confidence: 84%
See 1 more Smart Citation
“…The median total air kerma was significantly reduced after institution of lower fluoroscopy rates, with 22% and 32% reduction in diagnostic and interventional procedures, respectively. Similar to the study by Pyne et al, 13 fluoroscopy times were not influenced by the change in pulsed frame rate. Tube angulation previously has been shown to be an important factor in radiation exposure.…”
Section: Data Supporting the Use Of Lower Pulsed Frame Ratessupporting
confidence: 84%
“…Pyne et al, 13 taking advantage of a catheterization laboratory quality improvement initiative to reduce radiation, performed a retrospective review of angiographic image quality and radiation measures before and after implementation of a default digital pulse fluoroscopy and cine-acquisition rate of 10 FPS. The standard dose cohort (15 FPS) was compared with the reduced dose cohort for total x-ray dose in air kerma (mGy), fluoroscopy time, and contrast use.…”
Section: Data Supporting the Use Of Lower Pulsed Frame Ratesmentioning
confidence: 99%
“…In addition, procedural success and operative complication rates were comparable, and there was no case in which we changed the frame rate during the procedure. Previous studies on this topic did not report any increases in either the contrast volume or fluoroscopy time with low frame fluoroscopy (9,10), and the image quality score has previously been indicated to be comparable (5,6). Thus, with advances in technology, the flickering that occurs as a result of the low frame rate is no longer considered to be a problem.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, several studies have revealed that new X-ray imaging technologies can reduce radiation exposure while maintaining image quality (5,6). The use of low frame rate fluoroscopy at 7.5 frames per second is an important advancement with the potential to reduce radiation exposure; however, the effectiveness of these technologies in reducing radiation exposure has not been separately analyzed (3,7).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to reduce dose to patients, including meticulous X-ray technique and adherence to the principles of As Low as Reasonably Achievable (ALARA) will, by definition, reduce total operator dose 12 13. Important components of the radiation dose set by the equipment manufacturer include the current and pulse width 14. These parameters are difficult to change, however, once the equipment is installed.…”
Section: Introductionmentioning
confidence: 99%